2021
DOI: 10.3389/fphar.2021.663774
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gremlin 1 Prevents Intestinal Fibrosis Progression by Inhibiting the Fatty Acid Oxidation of Fibroblast Cells

Abstract: Intestinal fibrosis is a consequence of continuous inflammatory responses that negatively affect the quality of life of patients. By screening altered proteomic profiles of mouse fibrotic colon tissues, we identified that GREM1 was dramatically upregulated in comparison to that in normal tissues. Functional experiments revealed that GREM1 promoted the proliferation and activation of intestinal fibroblast cells by enhancing fatty acid oxidation. Blocking GREM1 prevented the progression of intestinal fibrosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Clinical research found that plasma saturated fatty acids was associated with the incidence of sudden cardiac death in patients suffering hemodialysis, which was largely dependent on the impairment of FAO in CKD patients and animal models with tubulointerstitial fibrosis [56]. FAO has also been shown to directly promote cell-mediated ECM degradation especially through PPAR, a ligand-activated nuclear hormone receptor that binds to specific DNA response elements to regulate gene transcription and control a plethora of cellular functions associated with fibrosis-related processes, which is countered by TGFβ in nearly all fibrotic tissues, including those of the lung, liver, kidney, and bowel [24, 57, 58]. There are three main isoforms of PPAR (α, δ, and γ), with tissue-dependent expression and variables but overlapping roles in fatty-acid uptake, lipid metabolism, mitochondrial biogenesis, and adipogenesis.…”
Section: Metabolic Adaptions Of Fibroblast Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical research found that plasma saturated fatty acids was associated with the incidence of sudden cardiac death in patients suffering hemodialysis, which was largely dependent on the impairment of FAO in CKD patients and animal models with tubulointerstitial fibrosis [56]. FAO has also been shown to directly promote cell-mediated ECM degradation especially through PPAR, a ligand-activated nuclear hormone receptor that binds to specific DNA response elements to regulate gene transcription and control a plethora of cellular functions associated with fibrosis-related processes, which is countered by TGFβ in nearly all fibrotic tissues, including those of the lung, liver, kidney, and bowel [24, 57, 58]. There are three main isoforms of PPAR (α, δ, and γ), with tissue-dependent expression and variables but overlapping roles in fatty-acid uptake, lipid metabolism, mitochondrial biogenesis, and adipogenesis.…”
Section: Metabolic Adaptions Of Fibroblast Activationmentioning
confidence: 99%
“…Acylcarnitine (derived from FAO by CPT1), acetyl-CoA, and fatty-acid β-oxidation breakdown products were greatly elevated. Concordantly, markedly enhanced oxygen consumption rate and expression of FAO-related genes in fibroblast cells was detected [58]. Therefore, FAO alterations in fibroblasts may differ from each other due to different organ tissues, providing diverse targets for perturbation of fatty-acid metabolism.…”
Section: Metabolic Adaptions Of Fibroblast Activationmentioning
confidence: 99%
“…In addition, GREM1 encoding gremlin-1 is a member of the BMP (bone morphogenic protein) antagonist family. Gremlin-1 has been demonstrated to promote the proliferation of intestinal fibroblasts [ 58 ]. Likewise, overexpression of Gremlin-1 has been shown to entail TGF-β pathway elevated ECM production and myofibroblast transition [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gremlin-1 (GREM1) belongs to the family of BMP antagonists and is upregulated in mice and clinical patients with pulmonary fibrosis [ 14 , 15 , 16 ]. An increasing number of studies have demonstrated that GREM1 has a profibrotic effect and contributes to pulmonary fibrosis [ 15 , 16 , 17 , 18 ], renal fibrosis [ 19 ] and colonic fibrosis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%